DIGITAL TRANSFORMATION OF JUSTICE AND ITS IMPACT ON COMMERCIAL JUDICIARY - Timush, Iryna; Drupp, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is to identify the main trends in the digital transformation of justice and its impact on the implementation of economic justice. Research methods: comparative analysis is applied to the study of legal acts and other sources relating to the topic under study; statistical method is used to obtain and process statistical data on the results of the use of digital technologies in economic proceedings. Results: the author finds out that the prospects for digital transformation of economic proceedings depend on improving the regulatory framework, ensuring cybersecurity, improving the technical support of the court and introducing mandatory registration of all participants to the court proceedings in the Unified Judicial Information and Communication System. The author emphasises that the quality of further digitalisation of economic proceedings depends on coordinated communication between the State, society and business. The specifics of commercial dispute resolution have revealed the expediency and demand for holding court hearings via videoconferencing outside the courtroom. Discussion: E-justice provides a number of advantages that can be used by participants in the economic process, reduces the risks of corruption in courts, and forms a new culture of procedural relations. It is necessary to constantly improve the skills of working with the subsystems (modules) of the EJICS.